High-performance liquid chromatographic determination of deoxycytidine monophosphate and methyldeoxycytidine monophosphate for DNA demethylation monitoring: experimental design and artificial neural networks optimisation - Havlis, J; Madden, J E; Revilla, A L; Havel, J (Journal of chromatography. B, Biomedical sciences and applications, 2001)
The optimal conditions for the separation of 2'-deoxycytidine-5'-monophosphate and 5-methyl-2'-deoxycytidine-5'-moncphosphate in the matrix of other natural occurring nucleotides after digest of DNA were investigated. Using experimental design combined with artificial neural networks, efficient optimisation of the HPLC separation conditions was performed. The mobile phase composition was optimised on the basis of its three components (concentration of phosphate, content of methanol and pH). The best separation was obtained with a mobile phase containing 50 mM phosphate, pH 5.5 and 6% methanol. The final resolution achieved between 2'-deoxycytidine-5'-monophosphate and 5-methyl-2'-deoxycytidine-5'-monophosphate was equal to 2.78. Finally, the optimised system was successfully tested on the nucleotide mixture solution to determine the methylation state of 2'-deoxycytidine-5'-monophosphate in DNA in the search for FMR1 gene changes.
Keywords: vysokoúčinná kapalinová chromatografie; deoxycytidinmonofosfát; DNA Methylation; deoxycytidin; Neural Networks, Computer; Chromatography, High Pressure Liquid; Research Design; Deoxycytidine Monophosphate; výzkumný projekt; neuronové sítě; metylace DNA; Deoxycytidine